The Antibacterial Activity of Dayak Onion Ethanol Extract (Eleutherine Palmifolia (L.) Merr) and Red Ginger (Zingiber Officinale Rosc Var. Rubrum) on Growth Gi Tract Pathogen Bacteria - Tiara Dini Harlita; Ganea Qorry Aina (Poltekkes Kemenkes Mataram, 2023)
Antibiotic resistance in gastrointestinal bacterial infections can be overcome by alternatives using medicinal plants such as Dayak bulbs (Eleutherine palmifolia (L.) Merr) and red ginger rhizome (Zingiber officinale Rosc. Var. Rubrum). This study aims to examine the antibacterial activity of a combination of ethanol extracts of Dayak bulbs with red ginger rhizomes and the effectiveness of the extract combinations in inhibiting the growth of Pseudomonas sp. and Bacillus sp. This research is an experimental study with a completely randomized design (CRD) of one factor, namely a combination of ethanol extract of Dayak onion tubers and red ginger rhizomes with 4 variations of concentration 25, 50, 75, and 100 mg/mL at 2 ratios of the combination of 2:1 and 3:1 for 48 experimental units. Tests were carried out on bacteria Pseudomonas sp. and Bacillus sp. in vitro with agar diffusion technique (Kirby Bauer test), while the positive control was Chloramphenicol 30 μg / mL and the negative controls were sterile aquadest. Data analysis in this study used the ANOVA test. The results showed ethanol extract of dayak onion bulbs, red ginger rhizomes, and a combination of the two extracts have antibacterial activity so which can be inhibiting the growth of Pseudomonas sp. and Bacillus sp. The combination of ethanol extract from dayak onion bulbs and has the greatest antibacterial activity at a 3:1 combination of 56.95% against the growth of Pseudomonas sp. and 109.72% against the growth of Bacillus sp.